Acute adrenaline myocardial necrosis prevention by artificial lung ventilation in experimental settings - S. A. Sisakyan; N. F. Krasnikov; A. S. Sisakyan; A. B. Semerdzhyan; V. A. Oganyan (Российский кардиологический журнал)
In experimental settings, hystotoxic catecholamine doses depress cardiomyocyte contractility, induce arrhythmia, and heart arrest. Edema and hemorrhages in lung tissue and myocardium, myocardial hemomicrocirculation disturbances, significantly disturbed CO2, O2 partial pressure, and blood pH, plus increased acidosis are observed. Artificial lung ventilation (ALV) prevents fibrillation and heart arrest, edema and generalized lung hemorrhages after lethal catecholamine dose infusion. In addition, ALV prevents hypercapnia, acidosis, and increases blood oxygenation.